47 meters down [videorecording (DVD)] - Roberts, Johannes; Holt, Claire, 1988-; Moore, Mandy, 1984-; Johnson, Chris J., 1977- (Anchor Bay Entertainment : Lionsgate, 2017)
Two sisters vacationing in Mexico are trapped in a shark cage at the bottom of the ocean. With less than an hour of oxygen left and great white sharks circling nearby, they must fight to survive.